What Is the Attitude of Romanian Smallholders Towards a Ground Mole Infestation? A Study Using Topic Modelling and Sentiment Analysis on Social Media and Blog Discussions - Alina Delia Călin; Adriana Mihaela Coroiu (Animals)
In this paper, we analyse the attitudes and sentiments of Romanian smallholders towards mole infestations, as expressed in online contexts. A corpus of texts on the topic of ground moles and how to get rid of them was collected from social media and blog thread discussions. The texts were analysed using topic modelling, clustering, and sentiment analysis, revealing both negative and positive sentiments and attitudes. The methods used by farmers when dealing with ground moles involve both eco-friendly repellent solutions and toxic substances and pesticides. Even well-intentioned farmers are discouraged by crop and lawn damage, resorting to environmentally aggressive solutions. The study shows that the relationship between humans and moles could be improved by active education on effective ecological agricultural approaches.